Stability of coagulation assays performed in plasma from citrated whole blood transported at ambient temperature - Zürcher, Manuel; Sulzer, Irmela; Barizzi, Gabriela; Lämmle, Bernhard; Alberio, Lorenzo (Thrombosis and Haemostasis, 2008)
Many preanalytical variables affect the results of coagulation assays. A possible way to control some of them would be to accept blood specimens shipped in the original collection tube. The aim of our study was to investigate the stability of coagulation assays in citrated whole blood transported at ambient temperature for up to two days after specimen collection. Blood samples from 59 patients who attended our haematology outpatient ward for thrombophilia screening were transported at ambient temperature (outdoor during the day, indoor overnight) for following periods of time: <1 hour, 4–6, 8–12, 24–28 and 48–52 hours prior to centrifugation and plasma-freezing. The following coagulation tests were performed: PT, aPTT, fibrinogen, FII:C, FV:C, FVII:C, FVIII:C, FIX:C, FX:C, FXI:C,VWF:RCo,VWF:Ag, AT, PC activity, total and free PS antigen, modified APC-sensitivity-ratio, thrombin-antithrombin-complex and D-dimer. Clinically significant changes, defined as a percentage change of more than 10% from the initial value, were observed for FV:C, FVIII:C and total PS antigen starting at 24–28 hours, and for PT, aPTT and FVII:C at 48–52 hours. No statistically significant differences were seen for fibrinogen, antithrombin, or thrombin-antithrombin complexes (Friedman repeated measures analysis of variance).The present data suggest that the use of whole blood samples transported at ambient temperature may be an acceptable means of delivering specimens for coagulation analysis. With the exception of factorV andVIII coagulant activity, and total PS antigen all investigated parameters can be measured 24–28 hours after specimen collection without observing clinically relevant changes.
Keywords: Coagulation factors; thrombophilia; laboratory; preanalytic